STUDI KASUS SIKAP EMPATI ANAK KELOMPOK B DI TK MUSLIMAT NU 14 NURUL HUDA KARANGDUREN - Dwi Handini, Nur Santi (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2020)
This study aims to finding out an overview of an empathy attitude of children in group B, knowing the factors that influence an empathy of children in group B, finding out the efforts of the teachers and the parents in developing empathy for children in group B, and finding out the results of developing children empathy attitudes group B by teachers and parents. Based on the theory and the problem of this study, the importance of cultivating the ability to empathy from an early age, so that children are able for social interaction positively, for example knowing the feeling of their friends, respecting the opinions of others and not discriminating against friends. The data collected by an interview, observation, and documentation of the problems that occurred. The research method used is a qualitative research approach with a single case study research type. The results of this study illustrated that the empathy of group B children has begun to develop, but there is one aspect that has not yet emerged, so the teachers and parents need to habituate and set an example both at home and at school.